Assessing field change through the expression of cytokeratin 18 and 19 in areas of erosive oral lichen planus and adjoining normal mucosa - Sam Prasad Prabakaran; Arvind Muthukrishnan (Wolters Kluwer Medknow Publications, 2018)
Introduction: Oral lichen planus (OLP) is a potentially malignant disorder. Of its seven different clinical forms, erosive is most prone for malignant transformation. The concept of field cancerization postulates that the mucosa of upper aero-digestive tract has a potential for developing malignancy due to genetic abnormalities and migration of transformed cells. Cytokeratins (CKs) are intermediate filament proteins that are specifically expressed in epithelial tissues and used as tools in diagnostic pathology, particularly in the detection of tumors. Aim: To identify field change through the expression of CK 18 and 19 in areas of erosive OLP and adjoining normal mucosa (ANM) and assess whether CK 18 and 19 could predict malignant transformation. Materials and Methods: Tissue samples from 19 patients with erosive OLP were subjected to immunohistochemical analysis for CK 18 and 19. Results: CK 18 was expressed in 11 out of the 19 samples of erosive OLP, of which nine samples showed expression in ANM as well. CK 19 was expressed in 10 out of the 19 samples of erosive OLP, of which eight samples showed expression in ANM as well. Conclusion: Expression of CK 18 and 19 could be used to predict malignant transformation of erosive OLP and also aids in assessing field change.